PENINGKATAN EDUCATIONAL QUALITY ASSURANCE (EQA) MELALUI SARANA DAN PRASARANA DI LEMBAGA PENDIDIKAN ISLAM MADRASAH TSANAWIYAH NEGERI 4 KARAWANG - Akbar Nursyabani; Tajuddin Tajuddin; Nur Astuti Darmiyanti (Universitas Pakuan, 2021)
IMPROVING EDUCATIONAL QUALITY ASSURANCE THROUGH FACILITIES AND INFRASTRUCTURE AT ISLAMIC EDUCATION INSTITUTIONS MADRASAH TSANAWIYAH NEGERI 4 KARAWANG Educational facilities and infrastructure are an important part of achieving a maximum quality of education, the minimum standard of facilities and infrastructure for MTs or SMP is contained in the Regulation of the Minister of National Education number 19 of 2005. This study aims to empirically determine the effect of management of facilities and infrastructure on quality of education services at Madrasah Tsanawiyah Negeri 4 Karawang. In this study, the authors used the quantitative method with statistical processing using the Spss V.18 software with multiple linear regression formulas, because the independent variables in this study were double or two. Collecting data using observation techniques, documentation and questionnaire instruments / questionnaire with a Likert scale method of 1 to 4. The population of this study were all teachers and staff, totaling 49 people, with a sample size of 44 respondents. Sampling using purposive sampling technique, while the data analysis technique using descriptive statistics, inferential statistics using multiple linear regression consulted using correlative statistics. The results of data processing can be concluded that simultaneously the management of facilities and infrastructure has a significant effect on the quality of education services with the results of the F test of 1228.07 which is interpreted to the F table of 3.2, then F count F table. While the correlation coefficient value obtained is 0.996, if interpreted to the guideline table for the correlation analysis scale, it has a very strong relationship level of 99.6%. Thus it can be argued that the management of facilities and infrastructure greatly affects the quality of education services at MTsN 4 Karawang in the 2020/2021 school year.